First report of Monoeca in Argentina, with description of two new species (Hymenoptera: Apidae) - Torretta, Juan Pablo (2016)
Two new species of the oil-collecting bee genus Monoeca Lepeletier & Audinet-Serville (Apidae: Tapinotaspidini) are described and figured from females and males captured in north - eastern Argentina. The two new species here described, Monoeca armata Torretta & Roig-Alsina, new species, and M. puchella Torretta & Roig-Alsina, new species, are easily distinguished from each other by the color of the integument, the wings, and the pilosity. Their relationships to al - ready described species of the genus are discussed. Monoeca were the only genus of Tapinostaspi - dini not known to occur in Argentina. The flower records and the study of the pollen scopal loads corroborate the association of these oil-collecting bees with p lants of the family Malpighiaceae.